Who should be charged? Principles for fair allocation of electricity system costs - Conall Heussaff; Eva Jüngling; Simone Tagliapietra; Georg Zachmann (Bruegel, 2025)
The high costs in the European Union of supplying electricity can only be structurally reduced through decarbonisation and deeper European electricity system integration. In the short-term, policymakers have few choices. They can redistribute system costs by shifting components from one consumer to another. Another immediate distributional option would be to reduce energy taxation, implicitly shifting costs to the taxpayer. Meanwhile, decision-making processes that translates electricity system costs into final consumer prices are fragmented. Rules on the short-term production, transmission and consumption of electricity are determined at EU level. National regulators and governments determine how the fixed costs of the system are recovered from consumers, while national policymakers also set energy taxes. This Policy Brief sets out options for shifting the fixed costs of the electricity system between consumers, for changing energy taxation to reduce prices and for evaluating systemic trade-offs between system cost and other characteristics, such as sustainability and reliability. We also estimate the quantitative effects of shifting costs between consumers and reducing taxes on electricity. We set out four principles for pricing electricity fairly. Policy interventions in the electricity system should not seek to achieve broader economic objectives at the expense of energy-policy goals. Consumer prices should incentivise efficient system operation. Carbon emissions should be priced in. The fixed costs of the electricity system should be primarily recovered from inelastic consumption. European policymakers should develop transparent analytical tools to assess the distributional effects of electricity-policy interventions. Lessons should be learned from the energy crisis, during which EU and national policies attempted to shield consumers from price impacts, and these lessons should form the basis of ongoing efforts to reduce prices. EU guidelines for electricity cost recovery should be established, following fundamental economic principles, and could form a policy toolbox for national governments to reduce energy prices. Finally, the long-term strategic goal of deeper physical and institutional integration of the European electricity should be pursued to structurally reduce electricity prices.
Keywords: 330